Is Radiofrequency Ablation Better than Venous Stripping for Management of Chronic Venous Insufficiency? - Reynaldo Halomoan; Leonard Christianto Singjie; Jonny Setiawan (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Chronic venous insufficiency (CVI) is a disease of the vein due to valve dysfunction, venous obstruction, or both. This results in increased vein pressure and related to disruption in the vein system.